2021
DOI: 10.1021/acsami.0c19608
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Free and Support-Free 3D Printing of Thermosetting Polymers with Isotropic Mechanical Properties

Abstract: The democratization of thermoplastic 3D printing is rooted in the ease of processing enabled by economical melting and shaping. Thermosetting polymers, on the other hand, have not enjoyed this advantage given that thermosetting resins cannot hold their shape without cross-linking or excessive fillers, and once cross-linked, they cannot be extruded for printing. Due to this formidable challenge, thus far, 3D printing of thermosetting polymers has been limited to the photopolymerization of specialized photosensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…No indication of partial crosslinking was observed. 39 The glass transition phenomenon was observed for all resins in the temperature range of 325-344 • C. Specifically, the T g was obtained to be 343.7 • C for the pure resin. By increasing the catalyst concentration from 1% to 4%, the T g decreased from 334.7 to 324.8 • C.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…No indication of partial crosslinking was observed. 39 The glass transition phenomenon was observed for all resins in the temperature range of 325-344 • C. Specifically, the T g was obtained to be 343.7 • C for the pure resin. By increasing the catalyst concentration from 1% to 4%, the T g decreased from 334.7 to 324.8 • C.…”
Section: Resultsmentioning
confidence: 83%
“…Also, For 3D printing, we followed the recently reported method based on extrusion of the preceramic polymer into a thixotropic bath. 18,39 Briefly, in this process, 3D printing is enabled by dispensing the preceramic polymer at the tip of a moving nozzle into a bath that can reversibly switch between fluid and solid states, and the subsequent thermal crosslinking of the printed part at once inside the bath (Figure 6A). The bath converts to fluid at the tip of the moving nozzle, allows the preceramic polymer to be dispensed, and quickly returns to a solid-state to maintain the geometry of the printed polymer both during printing and the subsequent high-temperature (180 • C) crosslinking (Figure 6B,C, and E).…”
Section: Resultsmentioning
confidence: 99%
“…Note that the speed mentioned here includes both printing and curing processes; our proposed method does not require a post‐curing step as opposed to traditional curing schedules, which require up to 12–24 h in an oven. [ 14 ] The resulting sample is a cured structure with dimensions of 34 × 5 mm ( Figure a). We also prove that this technique can be used to create 2D shapes.…”
Section: Resultsmentioning
confidence: 99%
“…Extrusion‐based printing of thermosets has been made possible by printing inside a thixotropic support bath, followed by extraction from the bath and curing in an oven. [ 14 ] Other studies have shown that direct ink writing coupled with UV‐assisted curing can be used to 3D print light‐sensitive resins. [ 15,16 ] Studies have also added viscosity‐modifying agents to make the resin shear‐thinning.…”
Section: Introductionmentioning
confidence: 99%
“…These materials offer a unique advantage that allows us to combine the desirable characteristics of geometrical structures and the intrinsic properties of constituent materials, thus providing the ability to improve or reach new mechanical performance levels not achievable with bulk materials. , Illustrative examples may include helical springs that can magnify the elastic stretch of a material by a factor of 1000, metallic microlattices that have very low mass and high specific strength, and structures that exhibit lateral expansion when pulled in one direction, e.g., negative Poisson ratio materials . The recent advances in 3D-printing technology have propelled the research and development of architected metallic materials with novel properties to a new height. , …”
Section: Introductionmentioning
confidence: 99%